Water sorption thermodynamic properties applied to persimmon skin and pulp - Telis, V. R. N. [UNESP]; Gabas, A. L.; Menegalli, F. C.; Telis-Romero, J. [UNESP] (Elsevier, 2000)
Moisture equilibrium data of persimmon skin and pulp were determined using the static gravimetric method. Adsorption and desorption isotherms were obtained in the range of 20-70°C, to water activities (a w) from 0.02 to 0.85. The application of the GAB model to the experimental results, using direct nonlinear regression analysis, provided a good agreement between experimental and calculated values. The net isosteric heat of sorption was estimated from equilibrium sorption data, using the Clausius-Clapeyron equation. Isosteric heats of sorption were found to increase with increasing temperature and could be well adjusted by an exponential relationship. The enthalpy-entropy compensation theory was applied to sorption isotherms and plots of ΔH versus ΔS for skin and pulp provided the isokinetic temperatures, indicating an enthalpy controlled sorption process. © 2000 Elsevier Science B.V.
Keywords: Isotherms; Moisture content; Persimmon; Thermodynamic properties